The prevalence of Trichomonas vaginalis and Candida albicans infection in the lower genital tracts of antenatal patients in Abakaliki, Southeastern Nigeria - Sunday-Adeoye, IM; Adeoye, JOK; Umeora, OUJ; Okonta, PI (Nepal Journal of Obstetrics and Gynaecology, 2010)
Aims: To determine the prevalence of Trichomonas vaginalis and Candida albican infection among an asymptomatic pregnant population and to document their pregnancy outcomes. Methods: This was a prospective study involving antenatal clinic attendees at the Ebonyi State University Teaching Hospital, Abakaliki, Nigeria. They were randomly recruited and informed consent obtained. Vaginal specimens were collected from them and analyzed in the laboratory. They were followed up till delivery and pregnancy outcomes documented. Results: Two hundred expectant mothers were recruited. The prevalence rate of Trichomonas vaginalis and Candida albicans were 0.5% and 27.5% respectively. Due to the high dropout rate in the study, it was impossible to make any reasonable inference about the pregnancy outcomes associated with these conditions. Conclusion: There is probably the need for the use of more sophisticated methods for the detection of Trichomonas vaginalis. The existing methods in most laboratories in the country may not be adequate. There is also probably the need for a larger sample size and a stricter follow up of the patients in order to document any adverse pregnancy outcomes associated with these conditions. Keywords: Prevalence; Trichomonas vaginalis; Candida albicans; antenatal care DOI: 10.3126/njog.v4i1.3325 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 11-14